2012
DOI: 10.1007/s00268-012-1667-0
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Vocal Function Evaluation After Thyroidectomy Using Thyroidectomy Related Voice Questionnaire

Abstract: During the early postoperative period, 28.3 % of patients had vocal cord palsy or lower-pitched voices, which could be evaluated using a simple questionnaire. Therefore, early postoperative voice evaluation is important. Patients with nonlaryngeal disorders may be more sensitive than those with laryngeal disorders to laryngeal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 18 publications
1
49
0
10
Order By: Relevance
“…Twenty were excluded, and 16 studies were determined to be eligible for inclusion. Appendix 1 lists these 20 articles and the reason for their exclusion. No additional study was found from our search of the two bibliographies in previous reviews …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty were excluded, and 16 studies were determined to be eligible for inclusion. Appendix 1 lists these 20 articles and the reason for their exclusion. No additional study was found from our search of the two bibliographies in previous reviews …”
Section: Resultsmentioning
confidence: 99%
“…Twenty were excluded, and 16 studies 3,5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] were determined to be eligible for inclusion. Appendix 1 lists these 20 articles [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and the reason for their exclusion. No additional study was found from our search of the two bibliographies in previous reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Hypocalcemia was defined as a case receiving calcium replacement therapy to reduce hypocalcemic symptoms, or with a serum calcium level ,8.0 mg/dl, or ionized calcium level ,1.13 mmol/l RLNP was defined as the presence of hoarseness or vocal cord palsy confirmed post-operatively by an otolaryngologist by laryngoscopic evaluation, thyroidectomy-related voice questionnaire administration, and acoustic and perceptual analyses, which was described in the previous study (15). Transient and permanent complications were defined with a cut-off time of 6 months.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…The TVQ is a self-assessment tool that measures voice quality after thyroidectomy; the TVQ was developed and validated in our institution [ 18 , 19 , 20 ]. It consists of 20 questions exploring voice symptoms ( n = 10) and swallowing and laryngopharyngeal reflux ( n = 10).…”
Section: Methodsmentioning
confidence: 99%